Ever-present threats from information technology: the Cyber-Paranoia and Fear Scale - Mason, Oliver J.; Stevenson, Caroline; Freedman, Fleur (Frontiers in Psychology, 2014)
Delusions involving technology, and specifically the internet, are increasingly common, and fear-reality statistics suggest computer-related fears are very widespread. These fears form a continuum from the widely understandable and realistic to the unrealistic, and frankly paranoid. The present study investigated the validity of this construct in a non-clinical population by constructing a novel self-report measure. The new Cyber-Paranoia and Fear Scale aims to measure the perception of information technology-related threats originating from or enabled by computers, smartphones, social networks and digital surveillance. Psychometric properties of the new Cyber-Paranoia and Fear Scale are reported alongside an established measure of suspiciousness and paranoia in 181 participants including a sub-group of fifty information technology professionals. Exploratory factor analysis suggested the presence of two, related, dimensions that we term Cyber-Fear and Cyber-Paranoia. Both sub-scales were internally consistent and produced a normal distribution of scores. The relationships of the sub-scales with age, gender, trait paranoia, digital literacy and digital inclusion are supportive of construct validity. The distinctiveness of ‘cyber-paranoia’ from general trait paranoia appears to mirror the clinical distinctiveness of ‘internet’ and other technology fuelled delusions. Knowledge provision to increase technological proficiency and awareness may bring about a reduction in cyber-paranoia.